1997
DOI: 10.1037/0097-7403.23.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Language-naive chimpanzees (Pan troglodytes) judge relations between relations in a conceptual matching-to-sample task.

Abstract: Three chimpanzees with a history of conditional and numeric token training spontaneously matched relations between relations under conditions of nondifferential reinforcement. Heretofore, this conceptual ability was demonstrated only in language-trained chimpanzees. The performance levels of the languagenaive animals in this study, however, were equivalent to those of a 4th animal-Sarah-whose history included language training and analogical problem solving. There was no evidence that associative factors media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
180
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(189 citation statements)
references
References 15 publications
(66 reference statements)
5
180
4
Order By: Relevance
“…Spontaneous analogical matching of relations between relations by chimpanzees, under conditions of nondifferential reinforcement, was reported by Thompson, Oden, and Boysen (1997). One of the animals in the study was Sarah, whose analogical capacities have already been described.…”
Section: Categorical Relational Matching By Nonhuman Primates and Chimentioning
confidence: 97%
See 1 more Smart Citation
“…Spontaneous analogical matching of relations between relations by chimpanzees, under conditions of nondifferential reinforcement, was reported by Thompson, Oden, and Boysen (1997). One of the animals in the study was Sarah, whose analogical capacities have already been described.…”
Section: Categorical Relational Matching By Nonhuman Primates and Chimentioning
confidence: 97%
“…So, why did these young chimpanzees fail to categorically match analogical relations? Perhaps they lacked requisite exposure to the presumed facilitative effects of symbol training and labeling on the relational recoding that was experienced by other chimpanzees and children (e.g., Rattermann & Gentner, 1998;Thompson et al, 1997).…”
Section: Implicit or Tacit Detection Of Analogical Relations By Childmentioning
confidence: 99%
“…Such relational requirements have been tested in a conceptual matching-to-sample task (a modified version of an analogy problem) proposed to chimpanzees with previous training with conditional and numerical tokens (Thompson et al, 1997). Four of the five subjects were successful at conceptually matching relations between relations, even though they were provided with no explicit training via differential feedback on each trial.…”
Section: Categorisation Of Abstract Relationsmentioning
confidence: 99%
“…After learning this discrimination, the degree to which this behavior transfers to novel situations having same and different relations is taken as evidence of concept formation. Using this choice task, it has been found that pigeons, parrots, rhesus monkeys, baboons, and chimpanzees are capable of learning and applying a S/D concept across a wide variety of simultaneously presented visual elements (Bovet and Vauclair, 2001;Cook, 2002a,b;Cook et al, 1995Cook et al, , 1999Cook and Wixted, 1997;Katz et al, 2002;Pepperberg, 1987;Thompson et al, 1997).…”
mentioning
confidence: 99%